Development of Dartboard Math Learning Media on Large Whole Numbers Material for Class IV Students - Aryati, Eka; Mulyawati, Ima (Lectura : Jurnal Pendidikan, 2024)
Learning large whole numbers in elementary schools is generally given abstractly using conventional methods by educators so many students experience difficulty in solving the problems given. This research aims to create learning media that can help students solve several problems related to large whole numbers. The Dartboard Math learning media developed in this research is in the form of a box in which there is a circle board with categories of large whole number values. The method used was the Research and Development (R&D) method using the 4D development model. This research has carried out product trials by 27 class IV students at SDN Jakarta Timur. The result showed that the Dartboard Math media has demonstrated validity in the media aspect and material aspect with the same percentage of 92%, both of which are in the Very Appropriate category. This media has tested the practicality of products with a percentage of 89% falling into the Very Practical category. User respondents produced an average percentage of product attractiveness index of 89%, including the Very Attractive category. Based on these results, it can be seen that the Dartboard Math learning media is valid, practical, and effectively used as a learning media that can help the mathematics learning process in large whole number material.